Status stock and Sustainable Management Measures for Moroccan Sardines - Mounir, Abdelaziz; Znari, Mohammed; Elmghazl, Hayat; Alahyane, Hassan; chouikh, Noreddine; Hichami, Nawal (Sustainable Marine Structures, 2021)
This article summarizes the state of stocks of sardine, sardina pilchardus in Moroccan waters at the end of 2016 and 2018. These stocks varies according to the region,They are now in a sustainable exploitation situation:Atlantic sardine, but also stocks that have reached or are still in over-exploitation levels: Mediterranean sardine. The fi shing pressure exerted on the sardine stock exceeds the optimal level by 40%. Due to the degradation of the fragile marine environment of the Mediterranean region, generated by pollution of various origins, the overexploitation of juveniles in the coastal strip, non-responsible practices and the use of non-fi shing gearselective, it is imperative to take the necessary measures to protect the marine environment and ensure rational and sustainable exploitation of the resource. (High commission plan 2006 report). ER